Conversations With Ogotemmeli: An Introduction to Dogon Religious Ideas - Griaule, Marcel; Dieterlen, Germaine (Oxford University Press, 1965)
English translation of Dieu d’eau: Entretiens avec Ogotemmêli (Paris: Editions du Chêne, 1948). This book was an international success; it describes, in the words of a sage among the Dogon of Mali, a cosmogony known only to intellectuals. Like other French anthropology of the period, the book drew attention to symbolic and philosophic elements of African thought to which Anglophones were insensitive. Recent research has been unable to confirm the existence of this cosmogony.
free